Analysis of Factors Influencing Sales Organization Effectiveness in State-Owned Banks in Bandung, West Java - Syahputra; Yogi Suprayogi; Rajiv Dharma Mangruwa (Yayasan Sinergi Kawula Muda, 2026)
Introduction/Main Objectives: This study analyzes the impact of sales management control strategies (SMCS), salesforce training (ST), and salesforce performance (SP) on the effectiveness of sales organizations (SOEs) in state-owned banks in Bandung, West Java. This study addresses the critical need to understand how digital technologies interact with the unique bureaucratic structures of the state-owned banking sector. Novelty: The novelty lies in the empirical testing of Salesforce Automation (SFA) as a moderation variable that bridges human resource development and strategic control. This research makes a theoretical contribution by examining whether automation improves the well-established managerial systems in traditional banking. Research Methods: Using quantitative methodology, data were collected from 350 sales managers at 3 state-owned banking institutions. Data was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test for immediate effects and moderation. Findings/Results: Findings show that SMCS, ST, and SP significantly and positively affect SOE, with ST emerging as the most dominant driver. Regarding moderation, SFA statistically strengthens the relationship between SMCS and ST and SOE. However, the effect of this interaction is modest in practical significance. Notably, SFA does not significantly moderate the relationship between SP and SOE. Conclusion: In the highly regulated banking sector, investing in human resources through systematic training remains more important to the success of an organization than technology adoption alone. SFA serves as a complementary and gradual tool that redefines the boundaries of efficiency without replacing the basic competencies of the salesforce.